The End of Cinema? : a Medium in Crisis in the Digital Age. - Gaudreault, André (Film and culture., 2015)
Is a film watched on a video screen still cinema? Have digital compositing, motion capture, and other advanced technologies remade or obliterated the craft? Rooted in their hypothesis of the 'double birth of media', André Gaudreault and Philippe Marion take a positive look at cinema's ongoing digital revolution and reaffirm its central place in a rapidly expanding media landscape.